Enhancing Signal Processing Measurement for Pulse Rate Variability by Novel Algorithm and Regression Technique - Velusamy, Saravanan; Murugan, Pallikonda Rajasekaran; Vishnuvarthanan, G.; Thiyagarajan, Arunprasath; Ramaraj, Kottaimalai; Kamalakkannan, Vidyavathi (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The researchers looked into the relationship connected with magnetic element and sunlight, further the overall duration & delays of parasympathetic nervous method reactions to variation in sunlight and magnetic activity. Heart Rate Variability (HRV) measures were connected with sunlight and magnetic parameters utilizing a multi-element linear regression model with Bonferroni correction of multi-comparison tests after removing the circadian impacts of both information.Changes in sunlight radiation intensity were linked to changes in Pulse rates, which we interpret as a physiologic reaction to stress. Solar radiation elevation, gravitational wave fluxes, and Schumann’s resonance amplitude were related to higher parasympathetic and HRV activity.HRV spectrograms were calculated for every participant utilizing Short Term Fourier Transform (STFT). A P-shift unfiltered fractional frequency response filter has utilized here, which gets smoother at P0. The filter is intended to provide a configurable median threshold that is excellent for slow ECG action and worse for rapid excursions. From the signal generator standpoint, it has been demonstrated that the flexible Unified Write Filter (UWFR) methodology in this technique provides optimal information extraction. In such a typical ECG signal sequence, the approach is necessary to track the T-wave, P-wave, and QRS-complex durations.